2013
DOI: 10.4236/jsbs.2013.34038
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Global Sustainable Development Based on Microalgae in Bio and Industrial Cycles, Management-Changing Decisions in Areas of Climate Change and Waste Management

Abstract: The paper provides requested management-changing decisions through implementation of conclusions of Global Sustainable Development theory based on including of microalgae in Bio and Industrial Cycles in the area of waste-related management challenges within creating market opportunities for industry through expansion of resource efficiency use across global supply chains and new design and building sustainable development with contemporary manufacturing of value added products. A truly coherent waste managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Aerobic wastewater treatment processes, such as activated sludge, are high cost systems because of the high energy inputs associated with the O 2 supply, the large amount of sludge that must be disposed of and the environmental impact resulting from the emission of greenhouse gases such as CO 2 . Currently, the use of microalgae–bacteria systems for wastewater treatment is particularly attractive because of their ability to produce inexpensive O 2 , to remove nutrients, pathogens, and heavy metals, and to fix CO 2 during a photoautotrophic process, which represents a considerable gain in the carbon available for CH 4 production compared with classic aerobic processes . Evaluation of the efficiency of microalgae–bacteria systems using wastewater in municipal facilities, piggery effluent, agro‐industrial and industrial wastewater have revealed good results in the removal of chemical oxygen demand (COD) and nutrients (phosphorous and nitrogen) and using high rate algal ponds (HRAP).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic wastewater treatment processes, such as activated sludge, are high cost systems because of the high energy inputs associated with the O 2 supply, the large amount of sludge that must be disposed of and the environmental impact resulting from the emission of greenhouse gases such as CO 2 . Currently, the use of microalgae–bacteria systems for wastewater treatment is particularly attractive because of their ability to produce inexpensive O 2 , to remove nutrients, pathogens, and heavy metals, and to fix CO 2 during a photoautotrophic process, which represents a considerable gain in the carbon available for CH 4 production compared with classic aerobic processes . Evaluation of the efficiency of microalgae–bacteria systems using wastewater in municipal facilities, piggery effluent, agro‐industrial and industrial wastewater have revealed good results in the removal of chemical oxygen demand (COD) and nutrients (phosphorous and nitrogen) and using high rate algal ponds (HRAP).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, WW biotreatment with microalgae is particularly attractive because WW is also an attractive resource for microalgae production because of its nutrient content and low cost coupled with an increased push to dramatically reduce the organics sent to landfill or pyrolysis; therefore, microalgae can play an important role in WW decontamination . Avagyan proposed that the application of microalgae for WW purification opens the possibility of alternative approaches that have the high stability that enables their use in concentrated and toxic environments. These alternative approaches also give high purification rate compared with activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effluent discharged into receiving water bodies is oxygenated. Furthermore, high‐value products can be extracted from the biomass, which contains protein and lipid …”
Section: Introductionmentioning
confidence: 99%
“…The use of petroleum fuel has caused the depletion of resources and emission of pollutant substances, and also caused environmental pollution, such as global warming and air pollution. To solve these issues, worldwide research has investigated alternative fuels and renewable energy from many bioresources as well as considering sustainable climate recycle systems . Among them, vegetable oil, animal fats, and spent frying oils, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, to ensure high product quality and user confidence, biodiesel standard have been established or are being developed in various countries around the world, including United State (ASTM D 6751) and Europe (EN 14214) . Besides studies on producing biodiesel from plant resources such as soybeans and palm oil, etc., there has also been research into obtaining biodiesel from marine microalgae, both at laboratory scale and industrial scale using cheap and waste resources . The marine and/or freshwater microalgae can produce high quality lipids for biodiesel production from relatively small land areas, it does not compete with agricultural food production, and reduces carbon dioxide emission into the air .…”
Section: Introductionmentioning
confidence: 99%